Measurements of mobile signal received power level at Ringlet, Cameron Highland, Malaysia - Suliman, S.H.; Hashim, W.; Ismail, Ahmad Fadzil; Zakariya, Mohd Azman; Yahya, A.S.; Sauti, M.S. (Science Publishing Corporation Inc., 2018)
Tenaga Nasional, the electric utility company in Peninsular Malaysia have been installing electronic meters that can establish wireless connectivity over the mobile phone network since 2005. Several locations including Ringlet, Cameron Highland have been pointed out as having difficulties in establishing a stable connection to the national main server. Empirical investigations had been carried out to determine the availability of service coverage and the associated signal received power levels at the said location. The findings are reported in this article. The outcomes from the measurement campaign were used to deduce the likely solution that is capable of establishing a more reliable link. Field trials involving installations of high-gain antennas and signal boosters as potential solutions were also carried out at selected sites within the district. It is the objective of the study to develop a total solution that can ultimately address the communication issue